2021
DOI: 10.1530/ec-21-0193
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of impaired bone quality in men with type 1 diabetes: a cross-sectional study

Abstract: Objective: Type 1 diabetes (T1D) is associated with a substantial fracture risk. Bone mineral density (BMD) is, however, only modestly reduced, suggesting impaired bone microarchitecture and/or bone material properties. Yet, the skeletal abnormalities have, however, not been uncovered. Men with TID seem to experience a more pronounced bone loss than their female counterparts. Hence, we aimed to examine different aspects of bone quality in men with T1D. Design and Methods: In this cross-sectional study, men w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…( 52 ) However, a recent study reported a less than 5% decrease in the median of bone material strength index (BMSi) measured with a reference point indenter (OsteoProbe) in a small cohort of males with T1DM compared to controls. ( 53 ) Interestingly, this finding is consistent with the reduction of cortical vBMD observed in our cohort with long‐standing T1DM. If the observed decrease in tissue material properties that constitute a necessary input for hFE analysis was confirmed, it would imply an overestimation of bone strength for the T1DM group by a similar amount of about 5%.…”
Section: Discussionsupporting
confidence: 92%
“…( 52 ) However, a recent study reported a less than 5% decrease in the median of bone material strength index (BMSi) measured with a reference point indenter (OsteoProbe) in a small cohort of males with T1DM compared to controls. ( 53 ) Interestingly, this finding is consistent with the reduction of cortical vBMD observed in our cohort with long‐standing T1DM. If the observed decrease in tissue material properties that constitute a necessary input for hFE analysis was confirmed, it would imply an overestimation of bone strength for the T1DM group by a similar amount of about 5%.…”
Section: Discussionsupporting
confidence: 92%
“…BMSCs were seeded on 24-well plates at a density of 2.5×10 4 were randomly divided into different groups. After 21 days of osteogenic induction, BMSCs were washed three times with PBS, fixed with 4% paraformaldehyde for 30 min, and incubated with Alizarin Red S (ARS) solution (Beyotime) for 10 min.…”
Section: Alizarin Red Stainingmentioning
confidence: 99%
“… 2 , 3 Compared with nondiabetic individuals, patients with T1DM exhibit lower whole-body bone mineral density, poorer bone mechanical strength, and a higher risk of osteoporosis and fracture. 3 , 4 Moreover, the decreased bone turnover and osteopenia in T1DM patients often result in impaired bone regeneration, making bone repair in these patients challenging. 5 The establishment of novel treatment regimens to improve bone formation under T1DM conditions is a matter of pressing concern.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study in this cohort, we reported that BMSi discriminates prior fracture and parental fracture [25]. Studies have also shown that mean BMSi is lower in groups with comorbidities known to affect fracture risk, such as, individuals with diabetes [31][32][33][34][35][36][37] or chronic kidney disease [38], and for those exposed to glucocorticoids [39].…”
Section: Discussionmentioning
confidence: 69%